Immune response genes receptors expression and polymorphisms in relation to multiple sclerosis susceptibility and response to INF‐β therapy. Issue 9 (27th June 2016) - Karam, Rehab A.; Rezk, Noha A.; Amer, Mona M.; Fathy, Hala A.
Abstract: Interferon (IFN)‐β is one of the disease modifying drugs used in the treatment of multiple sclerosis. A predictive marker that indicates good or poor response to the treatment is highly desirable. We aimed to investigate the relation between the immune response genes receptors (IFNAR1, IFNAR2, and CCR5) expression and their polymorhic variants and multiple sclerosis (MS) susceptibility as well as the response to IFN‐β therapy. The immune response genes receptors expression and genotyping were analyzed in 80 patients with MS, treated with IFN‐β and in 110 healthy controls. There was a significant decrease of IFNAR1 and IFNAR2 mRNA expression and a significant increase of CCR5 mRNA expression in MS patients compared with the control group. Also, the level of IFNAR1, IFNAR2, and CCR5 mRNA expression was found to be significantly lower in the responders than nonresponders. Carriers of IFNAR1 18417 C/C genotype and C allele had an increased risk of developing MS. There was a significant relation between CCR5 Δ32 allele and IFN‐β treatment response in MS patients. Our results highlighted the significance of IFNAR and CCR5 genes in multiple sclerosis risk and the response to IFN‐β therapy. © 2016 IUBMB Life, 68(9):727–734, 2016